The Historical Background of the Definition of Barbarism and its Occurrence in The Literary Texts - Sobirova Zarnigor Rakhimovna (Universitas Muhammadiyah Sidoarjo, 2022)
The article defines the word barbarism and its historical etymology. It studies its occurrence in the poetry and literature of the world.